(untitled) (Global Journal of Management and Business Research, 2019)
The study strives to explore individual income tax planning practices in Bangladesh using fieldlevel data from 194 assessees. The dichotomous procedure was used to score the items. Analytical results indicate that income tax planning scenario in Bangladesh was in a nascent state as compared to India. In Bangladesh, government and nongovernment employees invested more on investment than on philanthropic items and, they invested more in provident fund, benevolent fund, and group insurance, which were a mandatory for them. Deposit pension scheme (DPS), life insurance, and saving certificate were sequentially top ranking voluntary investment in Bangladesh, whereas life insurance was the highest investment in India. Income tax planning index (ITPI) was towering for tax knowledge seekers, self-return prepares, male and elderly respondents. A positive relationship was observed between tax awareness and individual tax planning that suggests more tax rules conscious individual assessee could enjoy maximum tax rebate in Bangladesh.